2012
DOI: 10.1016/j.polymer.2012.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Cationic photocured epoxy nanocomposites filled with different carbon fillers

Abstract: In this work, the effect of several carbon fillers, exfoliated graphite (EG), functionalized graphene sheets (FGS), multi-walled carbon nanotubes (MWCNTs), and oxidized multi-walled carbon nanotubes (f-MWCNTs), were compared on the curing process and physical properties of a cationically photocurable epoxy resin. The extent of the photopolymerization was monitored by Real-Time FTIR spectroscopy. It was found that all the nanofillers induced a delaying of the curing reaction probably due to a shielding effect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 21 publications
4
32
0
Order By: Relevance
“…Afterwards, the composite strength decreased with further increasing the TEG content. The results were in good agreement with the literature . A possible strengthening mechanism of TEG was the fact that the wrinkled surface of TEG at the nanoscale likely results in an enhanced mechanical interaction with the epoxy chains and, consequently, a strong interaction .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Afterwards, the composite strength decreased with further increasing the TEG content. The results were in good agreement with the literature . A possible strengthening mechanism of TEG was the fact that the wrinkled surface of TEG at the nanoscale likely results in an enhanced mechanical interaction with the epoxy chains and, consequently, a strong interaction .…”
Section: Resultssupporting
confidence: 89%
“…It is possible to observe that nanocomposites showed always higher T g values in comparing to the neat cured epoxy, evidenced by the shift of the maximum of tanδ peaks, together with a decrease of the damping. It is well known that in particulate‐filled polymers, the addition of rigid fillers can hinder the polymer chain movements and improve the crosslink density, leading to a damping decrement and a shift of T g values to higher temperatures . In this study, a significant reduction of damping (here evaluated as tanδ max ) was observed in the nanocomposites, together with a strong increment in T g values.…”
Section: Resultssupporting
confidence: 48%
“…Viscoelastic characterization of the composites showed that the filled materials always had higher T g values compared to the neat cured systems. It is noteworthy that all the fillers presented a reinforcing effect with an concomitant increase in the surface hardness values as shown by microindentation tests . In another publication, the same author investigated the effect of FGS in epoxy coatings cured by cationic photopolymerization .…”
Section: Cationic Uv‐curing Applicationsmentioning
confidence: 96%
“…This functionalization is known to enhance the interface and loadtransfer in CNTs/polymer nanocomposites. Commonly, solution method, a combination of dispersing CNTs in a liquid medium by sonication, mechanical, and magnetic stirring mixing by the polymer solution, and finally evaporating solvents is suggested to prepare a CNT-based UV-curable nanocomposite [7,19,54].…”
Section: Preparation Of Cnt-based Uv-curable Nanocompositesmentioning
confidence: 99%